PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA TENTANG PERISTIWA KEBANGSAAN SEPUTAR PROKLAMASI KEMERDEKAAN DI KELAS V SDI MAULAFA - K R. A. Ratu; Gerin Nobel Abineno (Universitas Nusa Cendana, 2023)
This study aims to improve student learning outcomes using cooperative learning models of the team game tournament type in learning about national events surrounding the proclamation of independence in fifth-grade students at SD Inpres Maulafa, Kupang City. This type of quantitative research uses a Pre-experimental Design, namely One Group Pretest-Posttest Design. The subjects of this research were 25 grade 5 students. Data was collected using observation and test techniques (Pretest and Posttest). The results of hypothesis testing, using a paired sample T-test showed that the significance value (2-tailed) was 0.000. This shows that at the significance level (2-tailed) <0.05. So it can be concluded that there is an influence of the cooperative learning model of the team games tournament type on the student's results in the national event material around the proclamation of independence in class V SD Inpres Maulafa.